Efficacy and Safety of Coblation-Assisted Endoscopic Surgery in the Management of Sinonasal Inverted Papilloma: A Retrospective Study - Omer, Goran Latif; Marzocchella, Giulia; Kareem, Rekawt Hama Rashid; Francavilla, Beatrice; Maurizi, Riccardo; Velletrani, Gianluca; Ahmed, Othman Hussein; Ahmed, Avar Fuad; Ali, Sahand Soran; Abdullah, Aland Salih; Gubari, Mohammed Ibrahim Mohialdeen; Di Girolamo, Stefano (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Inverted Papilloma (IP) is a benign but locally aggressive sinonasal epithelial tumor, characterized by a high recurrence rate and a risk of malignant evolution. Management of inverted papilloma depends on its size and extension: the endonasal endoscopic approach has become the most common because it allows effective removal of tumors with promising outcomes and lower morbidity. Despite the growing use of Radiofrequency Coblation (RFC) for some sinonasal surgical applications, the effectiveness of its use for endoscopic resection of intranasal and sinus tumors lacks consistency. The purpose of our study is to investigate the role of RFC in preventing recurrence in patients with inverted papilloma. Methods: We performed a monocentric, retrospective analysis of patients diagnosed with inverted papilloma of the nasal and paranasal sinus who underwent endoscopic sinus surgery. We subdivided the cohort into two groups: one consisted of patients who had undergone standard endoscopic sinus surgery, while the other one consisted of patients who had undergone coblation-assisted endoscopic sinus surgery. Results: Throughout a comprehensive 36-month follow-up period, 3 patients of Group A (17.6%) presented with IP recurrence, with 1 case identified at the 6-month mark and 2 cases at the 12-month interval. Conversely, Group B demonstrated a significantly reduced recurrence rate: in this group, no patient experienced IP recurrence at the same site during the follow-up period. Conclusions: Our findings provide valuable insights into the potential benefits of RFC, including a reduction in recurrence rates, when applied as an adjunctive tool in endoscopic treatment.